2011
DOI: 10.1186/1471-2393-11-96
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity knowledge prior to pregnancy: a survey study

Abstract: BackgroundOverweight and obesity are associated with increased risk for pregnancy complications. Knowledge about increased risks in overweight and obese women could contribute to successful prevention strategies and the aim of this study is to assess current levels of knowledge in a pregnant population.MethodsCross sectional survey of 412 consecutive unselected women in early pregnancy in Brisbane, Australia: 255 public women attending their first antenatal clinic visit and 157 women at private maternal fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 51 publications
4
42
3
5
Order By: Relevance
“…23 This study found that about 80% women knew that excess weight adversely affects reproductive health outcomes which was more than that reported by 75% participants in a study done in Brisbane, Australia 23 and 49% in Chicago, USA based study. 24 However the level of awareness in the present study was good only in about 10% participants in comparison to 49.8% reported in a study done in Nigeria while poor awareness in this study was seen in about 14% participants in comparison to 39.5% reported in the Nigerian study.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…23 This study found that about 80% women knew that excess weight adversely affects reproductive health outcomes which was more than that reported by 75% participants in a study done in Brisbane, Australia 23 and 49% in Chicago, USA based study. 24 However the level of awareness in the present study was good only in about 10% participants in comparison to 49.8% reported in a study done in Nigeria while poor awareness in this study was seen in about 14% participants in comparison to 39.5% reported in the Nigerian study.…”
Section: Discussionmentioning
confidence: 50%
“…15 Awareness of increased risk of caesarean deliveries was stated by 30.8% 15 26 of participants in other studies were more than our observations. The awareness of congenital anomalies among offspring was 23.7% in a study done in Chicago 15 and 58% in a study done in Brisbane 23 in comparison to 26.4% reported by participants in this study. Another Australian study observed that awareness of the role of obesity in maternal complications was much more for maternal than neonatal complications which was similar to our findings.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An Australian study [33] found that maternal education status is a main determinant of the extent of knowledge. Although we were unable to accurately determine the influence of education on participants’ extent of knowledge, we found that even participants who had demonstrated fair knowledge on the problems of maternal overweight and obesity, reported difficulty managing their weight during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the aforementioned adverse effects, Western studies [2733] from Australia, the USA, the UK have explored the perceptions of women during pregnancy, which targeted women who were White, Latina and African-American. For example, in a study [27] which compared perceptions of White women and African American women, it was found that African American women were more concerned with inadequate weight gain whereas White women more frequently expressed worry on excessive weight gain, and that the primary cited barrier of a healthy diet was the high cost of fresh produce.…”
Section: Manuscriptmentioning
confidence: 99%